Soybean (Glycine max) Extracts Impact on Plant and Soil Biology. Issue 15 (21st August 2016) - Ahmad, Naseer; Ullah, Faizan; Hussain, Ishtiaq; Ahmad, Khalid; Raza, Ghulam; Sajjadc, Yasar; Iqbal, Mazhar; Adil, Muhammad; Ali, Muhammad
ABSTRACT: The aim of the present investigation was to determine the phytotoxic effect of aqueous extract from fresh and oven-dried leaves and roots of soybean plants on maize growth and on rhizosphere soil. The extract prepared from fresh leaves of drought-stressed soybean plants significantly increased the accumulation of proline, soluble sugar, and endogenous abscisic acid (ABA) content of maize-treated plants. Increase in antioxidant activity like superoxide dismutase (SOD), peroxidase (POD), ascorbate peroxidase (APX), catalase (CAT), and endogenous ABA was recorded in treated plants. The soybean leaf extracts prepared from drought-stressed plants significantly decreased the soil pH and electrical conductivity (EC) of maize cultivated soil. The soybean drought-stressed leaf extracts prepared plants were found more effective in modulating the physiology of maize, indicating the higher allelopathic potential of soybean.